Supervening Events in Indonesian Commercial Contracts and Notes on the UNIDROIT PICC in Relation to COVID-19 Health Crisis - Tiurma M. P. Allagan; Dinda R. Himmah; Tazqia Aulia (Bank Indonesia, 2022)
The pandemic situation of COVID-19 has been affecting many sectors in our daily life, including law and economics. In regard to this matter, the issue of international commercial contract is significantly affected as well. It is well-known that the pandemic situation could be classified as a supervening event. This could be the basis to a party for not being able to fulfill a contractual obligation, or to postpone the fulfillment of such contractual obligation. However, different approaches of each national law of a State as well as what have been governed by several regulations might lead to multi-interpretation relating to whether COVID-19 shall be classified into force majeure or hardship. As one of UNIDROIT member states, it would be important to examine Indonesia's perspective towards this issue. Notably during the recent situation in which the increasing number of international commercial contracts involving Indonesian parties. This article would examine supervening events on international commercial contracts, especially in the perspective of Indonesian law.